2017
DOI: 10.3892/ol.2017.6519
|View full text |Cite
|
Sign up to set email alerts
|

Screening of candidate key genes associated with human osteosarcoma using bioinformatics analysis

Abstract: The aim of the present study was to identify the key genes associated with osteosarcoma (OS) using a bioinformatics approach. Microarray data (GSE36004) was downloaded from the Gene Expression Omnibus database, including 19 OS cell lines and 6 normal controls. Differentially expressed genes (DEGs) in the OS cell lines were identified using the Limma package, and differentially methylated regions were screened with methyAnalysis in R. Copy number analysis was performed and genes with copy number gains/losses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Thereafter, we utilized the R package circular binary segmentation algorithm in "DNAcopy." library for mapping DNA CNV data at the genetic level for all samples based on the segmented CNV data (Zhang et al, 2017). With regard to the DNA MET profiles, the β-values of the probe were filtered for eliminating probes positioned on the sex chromosomes.…”
Section: Methods Mrna Expression Patterns Dna Met and Dna Copy Numbersmentioning
confidence: 99%
“…Thereafter, we utilized the R package circular binary segmentation algorithm in "DNAcopy." library for mapping DNA CNV data at the genetic level for all samples based on the segmented CNV data (Zhang et al, 2017). With regard to the DNA MET profiles, the β-values of the probe were filtered for eliminating probes positioned on the sex chromosomes.…”
Section: Methods Mrna Expression Patterns Dna Met and Dna Copy Numbersmentioning
confidence: 99%
“…Zhang et al. ( 101 ) conducted bioinformatic analysis on 19 osteosarcoma cases and six normal samples obtained from the Gene Expression Omnibus database and compared the differentially expressed genes, differentially methylated regions, copy number, and functional enrichment of the two groups. The results showed that hypermethylation in the fragment crystallizable region of immunoglobulin (Ig) E, high-affinity I, receptor for γ polypeptide was significantly associated with osteosarcoma development.…”
Section: Cellsmentioning
confidence: 99%
“…In the previous studies, the limited number of samples and inappropriate analysis methods of multiple datasets led to deviation of the results. Zhang et al ( 9 ) and Diao et al ( 10 ) described the role of gene copy number alterations and methylation changes in the malignant progression of osteosarcoma using bioinformatics analyses, respectively. However, these studies were only based on single datasets and had a limited sample size, which may have biased the final results.…”
Section: Introductionmentioning
confidence: 99%